Population structure and diversity of the pathogenic fungus Aspergillus fumigatus isolated from different sources and geographic origins - Duarte-Escalante, Esperanza (2009)
Fil: Duarte-Escalante, Esperanza. Universidad Nacional Autónoma de México. Laboratorio de Micología Molecular; México.